The Perception of Indonesian Nursing Students on the Learning Environment in Clinical Practice - Pepin Nahariani; Fahruddin Kurdi; Ratna Puji Priyanti (Universitas Airlangga, 2018)
Introduction: The clinical practice environment students have multiple roles as learners and service providers. At this time students are faced with a fluctuating, complex environment and far from the predictions and controls of academic teachers. The aim of this study was to evaluate nursing student satisfaction and perception of the learning environment in clinical practice. Methods: This study used correlational analytic survey methods with cross-sectional approach. A total of 164 nursing student were selected using a convenience sampling. The data were collected in three schools of nursing in East Java. Data were obtained using the Bahasa version of the Clinical Learning Environment, Supervisions and Nurse Teacher (CLES+T). The instrument showed good validity and reliability. The data were analyzed using descriptive analytic, Spearman rho correlation and logistic regression. Results: Respondents were 164 students, clinical learning practice is mainly determined by the role of nurse teacher (M = 3.82; SD = 0.496). Student satisfaction obtained at 56.7%. There was a significant relationship between clinical practice learning and student satisfaction with p-value 0.000. The highest correlation value is the role of lecturer nurse (r = 0.544), with value R2 = 0.377, the coefficient of β adjusted highest to 2.075. Conclusion: According to student perceptions, the content of supervisory relations, the pedagogy atmosphere in the ward/room and the role of the nurse lecturer contributed greatly to creating a conducive clinical learning environment.